Environmental Conditions Modulate Warming Effects on Plant Litter Decomposition Globally - Sarah Schwieger; Ellen Dorrepaal; Matteo Petit Bon; Vigdis Vandvik; Elizabeth le Roux; Maria Strack; Yan Yang; Susanna Venn; Johan van den Hoogen; Fernando Valiño; Haydn J. D. Thomas; Mariska te Beest; et al. (Ecology Letters, 2025)
Empirical studies worldwide show that warming has variable effects on plant litter decomposition, leaving the overall impact of climate change on decomposition uncertain. We conducted a meta‐analysis of 109 experimental warming studies across seven continents, using natural and standardised plant material, to assess the overarching effect of warming on litter decomposition and identify potential moderating factors. We determined that at least 5.2° of warming is required for a significant increase in decomposition. Overall, warming did not have a significant effect on decomposition at a global scale. However, we found that warming reduced decomposition in warmer, low‐moisture areas, while it slightly increased decomposition in colder regions, although this increase was not significant. This is particularly relevant given the past decade's global warming trend at higher latitudes where a large proportion of terrestrial carbon is stored. Future changes in vegetation towards plants with lower litter quality, which we show were likely to be more sensitive to warming, could increase carbon release and reduce the amount of organic matter building up in the soil. Our findings highlight how the interplay between warming, environmental conditions, and litter characteristics improves predictions of warming's impact on ecosystem processes, emphasising the importance of considering context‐specific factors.